Philippine Tariff Reforms: A CGE Analysis - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 2000)
The Philippines undergoes a tariff reform program. After more than a decade of implementation, significant achievements have been attained in terms of changes in the tariff structure. For example, quantitative restrictions on important commodities have been tariffied. The tariff structure has been simplified from a multi-layered one into a structure with fewer tariff rates. Furthermore, tariff rates have been substantially reduced. The objective of the paper is to analyze the effects of the tariff reform program using a computable general equilibrium model calibrated using Philippine data. The primary focus is on the change in the tariff structure and its impact on efficiency, resource movements, income distribution, and welfare.
Keywords: 330; economic/development modelling; tariff; Zollpolitik; Reform; Allgemeines Gleichgewicht; Philippinen